2020
DOI: 10.1016/j.biopsych.2020.02.477
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Subfield and Amygdala Nuclei Volumes in Schizophrenia Patients With a History of Violence

Abstract: Schizophrenia (SCZ) is associated with an increased risk of violence compared to the general population. Previous studies have indicated smaller hippocampal and amygdala volumes in violent than non-violent psychotic patients. However, little is known about volumetric differences at the subdivision level of these structures. In the present study, hippocampal subfields and amygdala nuclei volumes were estimated with FreeSurfer from 3 T MRI of SCZ patients with (SCZ-V, n = 24) and without (SCZ-NV, n = 51) a histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
2
7
1
Order By: Relevance
“…In fact, they ranged from almost 11% (medial nucleus lh) to less than 2% (paralaminar nucleus rh) and showed focal maxima in subregions anatomically aggregated in the bilateral rostral-medial amygdala. Recent studies in major depressive disorder (Yao et al, 2020), obsessive-compulsive disorder (Zhang et al, 2020), posttraumatic stress disorder (Morey et al, 2020), and schizophrenia (Barth et al, 2021;Tesli et al, 2020;Zheng et al, 2019) have also documented differential alterations of amygdala subregions but spatial patterns differed from our findings. Importantly, despite limited comparability due to differing etiology, the medium-to-large effect sizes of amygdala nuclei reductions in acute AN found here substantially exceed the small effects previously reported under other neuropsychiatric conditions where widespread GM alterations are well-established, such as schizophrenia (van Erp et al, 2016).…”
Section: Discussioncontrasting
confidence: 85%
“…In fact, they ranged from almost 11% (medial nucleus lh) to less than 2% (paralaminar nucleus rh) and showed focal maxima in subregions anatomically aggregated in the bilateral rostral-medial amygdala. Recent studies in major depressive disorder (Yao et al, 2020), obsessive-compulsive disorder (Zhang et al, 2020), posttraumatic stress disorder (Morey et al, 2020), and schizophrenia (Barth et al, 2021;Tesli et al, 2020;Zheng et al, 2019) have also documented differential alterations of amygdala subregions but spatial patterns differed from our findings. Importantly, despite limited comparability due to differing etiology, the medium-to-large effect sizes of amygdala nuclei reductions in acute AN found here substantially exceed the small effects previously reported under other neuropsychiatric conditions where widespread GM alterations are well-established, such as schizophrenia (van Erp et al, 2016).…”
Section: Discussioncontrasting
confidence: 85%
“…The amygdala is often studied together with the hippocampus (15,25,27), as both structures are tightly and reciprocally connected and topologically intertwined (28).…”
Section: Introductionmentioning
confidence: 99%
“…The amygdala is often studied together with the hippocampus (15, 25, 27), as both structures are tightly and reciprocally connected and topologically intertwined (28). Abnormalities in the amygdala-hippocampus complex have been implicated both in schizophrenia (2) and bipolar disorders (13).…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews (Fjellvang, et al and Widmayer, et al) found volume differences in some areas such as prefrontal regions, temporal lobe, hippocampus, thalamus and cerebellum, lateral ventricles, amygdala, and putamen, and Tesli, et al showed differences in hippocampal subfields and amygdala nuclei volumes in violent patients with schizophrenia [16,19,37]. In addition, Storverstre, et al showed differences in cortical folding and cortical thickness in different cor-Nonetheless, this scoping review describes current research and provides information that could help researchers in future studies on this topic.…”
Section: Brain Function and Anatomymentioning
confidence: 99%
“…Li, et al found a relationship between Th17-related cytokine levels and the severity of schizophrenia and aggressive behavior. In addition, some studies found differences in gray matter volume, cortical morphology, and hippocampal volume in people with schizophrenia and violence [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%